Developing a battery of measures for unobtrusive indicators of organisational culture: a research note. Issue 1 (2nd January 2023) - Reader, Tom W.; Gillespie, Alex
Abstract: Measuring organisational culture is important for detecting the values and practices that increase organisational risk (e.g., unethical conduct). Self-report methods (e.g., surveys) are mostly used to study culture: however, due to reporting biases and sampling limitations, and the rapid advance of digital data, researchers have proposed unobtrusive indicators of culture (UICs; e.g., drawn from social media, company reports, executive data) as a supplementary methodology for identifying organisations at risk of failure. A UIC is a single measure of organisational culture drawn from data collected without engaging employees, and research using UICs is in its nascent stage. Although various data sources have been established for studying culture unobtrusively, researchers have yet to explore the application of multiple UICs drawn from different data sources. To investigate this, we developed an experimental battery of 83 UICs drawn from seven data sources (e.g., company earnings calls, employee online reviews, executive data), applying diverse analyses (e.g., natural language processing, quantitative analysis of behavioural data) to measure eight dimensions of culture (e.g., governance, integrity). We then applied the battery to assess 312 large European companies. We found that the UICs could distinguish between companies and different industries, and one dimension (customer focus) was associated with an outcome variable commonly used in culture research (Return on Capital Employed). However, we were not able to establish a coherent set of statistically reliable dimensions due to the clustering of UICs by data source. This clustering likely occurred because data sources reflected the values and practices of different stakeholders (e.g., employees, managers), which underscores a conceptualisation of culture that is focused less on shared values across an institution, and more on the values, priorities, and practices experienced by different sub-groups. Future research could structure UICs according to data sources and apply UICs to examine the causes of organisational failure.